1977
DOI: 10.1111/j.1365-2362.1977.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible sites of interaction of acute renal failure with amino acid utilization for gluconeogenesis in isolated perfused rat liver

Abstract: Experiments were performed to elucidate the mechanisms involved in the enhanced conversion of amino acids to glucose in acute uraemic rats. Increased gluconeogenesis from a mixture of serine, threonine, lysine, glutamate, ornithine and citrulline was confirmed using a non-recirculating perfusion system. Stimulation was concentration dependent, being most pronounced at physiological amino acid concentrations. Stimulation of glucose and urea formation could be mimicked by using serine alone whereas with lactate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Fröhlich et al [2,3] found a stimulation of gluconeogenesis in the presence of amino acids in liver per fusion experiments in acutely uraemic rats. Stimulation of glucose synthesis from serine in acute uraemia induced by a maximal activation of serine dehydratase has also been described by Fröhlich et al [4], Furthermore, serine may be important for the regulation of glycogen metabolism in skeletal muscle of acutely uraemic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Fröhlich et al [2,3] found a stimulation of gluconeogenesis in the presence of amino acids in liver per fusion experiments in acutely uraemic rats. Stimulation of glucose synthesis from serine in acute uraemia induced by a maximal activation of serine dehydratase has also been described by Fröhlich et al [4], Furthermore, serine may be important for the regulation of glycogen metabolism in skeletal muscle of acutely uraemic rats.…”
Section: Introductionmentioning
confidence: 99%
“…The key regulatory enzymes of ureagenesis and gluconeogenesis are located in the same zone of hepatic acinus, showing a parallel behavior of these pathways. Therefore, in the situations of high blood-urea concentrations, gluconeogenesis, in general (18), and from serine, in particular (27), are stimulated; meanwhile, when urea production is inhibited, gluconeogenesis (9) and even serine dehydratase also decrease. This relationship leads us to assume some degree of channeling between substrates and initial products of both pathways; for example, the carbon backbone of amino acids that give up their NH 3 group for urea synthesis is channelled to glucose production.…”
Section: Discussionmentioning
confidence: 99%
“…A large pro portion of the amino acids administered with the ENAA regimen was degraded to urea. This may be explained by experimental datas of Fröhlich et al [22,23], who demonstrated an enhanced propensity for the liver to catabolize circulating amino acids in acutely ure mic rats. Should these observations reflect the metabolic alterations obtained in humans with ARF, then one might predict that intra venous infusions of larger quantities of amino acids may lead to an enhanced rate of amino acid degradation in the liver [19], So, neither a great quantity of nitrogen intake nor the administration of a 50:50 ENAA solution seems to play the key role in reducing hypercatabolism.…”
Section: Reduction Of Negative Nitrogen Balance As a Current Principlmentioning
confidence: 99%